The conserved wobble uridine tRNA thiolase Ctu1 is required for angiogenesis and embryonic development. - Yangziwei Yu; Chuqiao Wang; Yan Wang; Heng Shi; Huiyuan Hu; Yibin Du; Zhaoli Zhou (PLoS ONE)
Cytosolic thiouridylase is a conserved cytoplasmic tRNA thiolase composed of two different subunits, CTU1 and CTU2. CTU2 serves as a scaffold protein, while CTU1 catalyzes the 2-thiolation at the 34th wobble uridine of the anticodon loop. tRNAGlnUUG, tRNAGluUUC, and tRNALysUUU are the tRNA substrates that are modified with a thiol group at the C2 positions (s2) by CTU1, and also with a methoxycarbonylmethyl group at the C5 positions (mcm5) by Elongator and ALKBH8. mcm5s2U34 modification of the three tRNAs, and their modifying enzymes are involved in human disease and development. Elongator mutant animals exhibit severe phenotypes, while the biological function of Ctu1 in vertebrate animal models remains poorly characterized. Here, we applied antisense morpholino oligonucleotides targeting cytosolic thiouridylase subunit1 (ctu1) transcripts in a zebrafish model and small interfereing RNA against CTU1 transcript in human endothelial cells to define the phenotypes. We found that deficiency of ctu1 causes impaired angiogenesis and development in zebrafish embryos, and CTU1 is involved in proliferation, migration, and tube formation of human endothelial cells. We employed single-cell RNA sequencing to acquire the transcriptomic atlas from ctu1 and control morphant zebrafish. Comprehensive bioinformatics analysis, including pseudo-time, RNA velocity, cell-cell communication, and gene regulatory network inference revealed that ctu1 deficiency leads to the arrest of cell cycle, and the defects of nerve development and erythrocyte differentiation and the attenuation of several pro-angiogenic signaling pathways, e.g., angpt-tek and dll4-notch. Our findings show for the first time that CTU1 is essential for angiogenesis and embryonic development in vertebrates.